Species diversity of Tetrigidae (Orthoptera) in Guizhou, China with description of two new species. Issue 13 (11th April 2017) - Ding, Jian-Hua; Wen, Ting-Chi; Wu, Xiao-Min; Boonmee, Saranyaphat; Eungwanichayapant, Prapassorn D.; Zha, Ling-Sheng
ABSTRACT: Guizhou Province, located in southwest China, is famous for its wholly karst landforms, in which many pygmy locusts with poor dispersal ability have been isolated and preserved. Species diversity of Tetrigidae from Guizhou is introduced, which deals with six sub-families, 28 genera and 69 species, among them, 33 species are endemic to Guizhou. Two new species, Paragavialidum prominemarginatus Zha & Ding sp. nov. and Teredorus jinshaensis Zha & Ding sp. nov. are described and illustrated with photographs. Flatocerus chishuiensis, Flatocerus nigritibialis and Flatocerus nigrifemura are considered as synonyms of Flatocerus wuyishanensis . Flatocerus wuyishanensis is redescribed and photographed based on our collections. www.zoobank.org/urn:lsid:zoobank.org:pub:334D6268-E3C1-450E-A3A2-31F9839B4EE6